Impact of climate services on Rwandan farmers: Summary of findings from the Rwanda Climate Services for Agriculture Project - Hansen, James (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Through the Rwanda Climate Services for Agriculture (RCSA) project, a consortium of national and international partners worked from 2016 to 2020 to strengthen the contribution of climate services to Rwanda’s farmers and agriculture sector. The project used a combination of communication channels to support farmers’ use of climate services. It adopted the Participatory Integrated Climate Services for Agriculture (PICSA) approach, developed by the University of Reading, to support farmers’ use of historical and forecast seasonal climate information. PICSA combines the use of local climate information with participatory resource mapping, activity calendars and budgeting activities. The participatory process was implemented at an unprecedented scale by training 2,111 local agricultural extension staff and volunteer Farmer Promoters within the Twigire Muhinzi agricultural extension system, who in turn trained and facilitated 112,767 farmers to use climate services. The project partnered with Radio Huguka – a community radio network with an estimated listenership of 3.1 million farmers – to develop climate service programming in several standard and interactive formats. Radio Listeners Clubs (RLCs) were piloted that combine the reach of broadcast media with the power of participatory processes. Building on existing PICSA groups, 225 Farmer Promoters were trained to lead their village groups in weekly meetings to listen and discuss climate service radio programs, participate in live call-in shows, share and record their plans to act on what they learned, and share the information with other farmers.